Embodiment of social roles and thinness as a form of capital: A qualitative approach towards understanding female obesity disparities in Chile. (March 2018) - Robinovich, Jossiana; Ossa, Ximena; Baeza, Bernardita; Krumeich, Anja; van der Borne, Bart
Abstract: Obesity in Chile disproportionately affects women of low socioeconomic status (SES). Research has shown that ideals of body size and differences in perceived social pressure for being slim across socioeconomic strata contribute to the social stratification of body size among women in modern societies. Thinness is most valued by high SES women, following western standards of ideal body size. Aiming to understand the link between ideals of body size and SES, this qualitative study explored how 36 Chilean women construct their bodily ideals according to their social position. A purposive sample of women with different profiles with regard to educational attainment, nutritional status and body size (dis)satisfaction was defined, aiming to cover a diverse spectrum of bodily perceptions. Data were collected through semi-structured interviews and approached through a thematic and narrative analysis. Drawing on Bourdieu's concepts of habitus, field, capital and embodiment of the social context, this study explains how ideals of body size and appearance are strongly linked to class-dependent gender roles and social roles. The existing gender and class inequalities in the Chilean social structure have been literally embodied by these women through a 'gendered class habitus'. Compliance with the thin ideal confers women different degrees of power according to their social position in different fields, such as in marriage and on the labour market, which turns thinness into an embodied form of capital. The societal dynamic behind obesity rates cannot be disregarded when approaching possible solutions. Promoting obesity-related lifestyle modification at an individual level might appear an over-simplistic and individualistic approach to a complex social issue. Context-oriented interventions that take cultural constructions of gender and social class into account might yield better results in the long term, while advocating for a more equitable society and social justice as a public health concern. Highlights: Obesity in Chile disproportionately affects women of low socioeconomic status (SES). Women's ideals of body size differ by SES in western societies. This qualitative study explored how women construct bodily ideals according to SES. Class-dependent gender and social roles influence women's ideals of body size.